SIMULATION PLATFORM IN TLM OF SYSTEM ON CHIP USING RETARGETABLE ISS - KHETATBA, M.; BOUDOUR, R. (Courrier du Savoir, 2014)
System-on-Chip  (SoC) designs are increasingly becoming more complex. One of the major constraints is the time to market New design methods are necessary, and the tendency is with the integration of the software and hardware parts on the same chip.  Efficient on-chip communication architectures are critical for achieving desired performance in these systems  Thus, the development of codesign’s modern methods and  the appearance of hardware description languages  (HDL) based on C/C++ such as SystemC or specC allowing to employ the same language to describe the software and the hardware, and returning of this fact easier and more effective Co-simulation. These methods would be able to generate an optimal solution starting from a functional specification by reducing the time and the cost of the design. Thus, one of the main objectives of this paper is the development  of  a SystemC  platform  for multiprocessors architectural exploration at  the compromise  level  (TLM) by using SystemC/TLM.  It must  lead  to partition  system  into hw/sw and also  to validate  it by simulation or  to move easily modules from hardware to software (or vice versa) during the architectural exploration. Except for the software task priorities that could be modified, we only need to recompile and simulate